Kegiatan ekstrakurikuler rohis sebagai sarana pendidikan karakter - Opnamiyati, Siti Hayani; Asrofi, Dien Amalina Nur (Educenter : Jurnal Ilmiah Pendidikan, 2022)
This study aims to determine the role of spiritual extracurricular activities in character education facilities. Currently, it is quite common for crimes committed by students, for example, brawls between students that cause death tolls, robbery and mistreatment of others and even teachers. Techniques for Data Analysis The research was carried out using deductive qualitative. The research was conducted using the literature study method. The results of the study indicate that to overcome delinquency in these students, it is necessary to activate the implementation of character education. One of them is through extracurricular activities Rohis, whose material is in line with 18 character values in character education.